2020
DOI: 10.1021/acs.inorgchem.9b03499
|View full text |Cite
|
Sign up to set email alerts
|

Selective Recovery and Detection of Gold with Cucurbit[n]urils (n = 5–7)

Abstract: Environmentally benign methods for gold recovery and detection are highly desirable for a sustainable future. Herein, we demonstrate a selective recovery and detection strategy of gold with cucurbit­[n]­urils (Q­[n = 5–7]) by means of outer-surface interactions. Tetrachloroaurate anion ([AuCl4]−) is able to be rapidly precipitated with Q­[n] in forms of supramolecular adducts. X-ray crystallography of four Q­[n = 5–7]·[AuCl4]− complexes reveal that strong outer-surface interactions between Q­[n = 5–7] and [AuC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 24 publications
0
25
0
Order By: Relevance
“…It is worth noting that Q[7] could encapsulate the [Au(H 2 O) 4 ] 3+ cation inside its cavity, to generate a rare [Au(H 2 O) 4 ] 3+ ⊂Q[7] inclusion complex. In addition, anti‐interference experiments revealed that Q[ n ]s ( n =5, 6, and 7) possessed high capture capacity and selectivity for [AuCl 4 ] − over other transition‐metal ions in aqueous solution [43a] . In 2020, Stoddart and co‐workers reported a highly efficient gold‐recovery protocol on the basis of the instantaneous assembly between Q[6] and [AuCl 4 ] − or [AuBr 4 ] − anions [43b] …”
Section: Applications In the Capture And Adsorption Of Hazardous Chemicalsmentioning
confidence: 99%
“…It is worth noting that Q[7] could encapsulate the [Au(H 2 O) 4 ] 3+ cation inside its cavity, to generate a rare [Au(H 2 O) 4 ] 3+ ⊂Q[7] inclusion complex. In addition, anti‐interference experiments revealed that Q[ n ]s ( n =5, 6, and 7) possessed high capture capacity and selectivity for [AuCl 4 ] − over other transition‐metal ions in aqueous solution [43a] . In 2020, Stoddart and co‐workers reported a highly efficient gold‐recovery protocol on the basis of the instantaneous assembly between Q[6] and [AuCl 4 ] − or [AuBr 4 ] − anions [43b] …”
Section: Applications In the Capture And Adsorption Of Hazardous Chemicalsmentioning
confidence: 99%
“…Cucurbit[ n ]uril (classical Q[ n ], n = 5–8, 10, and 13–15) have been shown to exhibit a wide range of potential applications in various fields, through leveraging the properties of this macrocyclic family and by the selection of a cavity with an appropriate size. Recent examples demonstrate this with targeted cell imaging [ 1 ], human cancer assay [ 2 ], Q[ n ]-based supramolecular frameworks (QSFs) [ 3 , 4 ], sensors [ 5 , 6 , 7 , 8 ], fluorescent imprintable hydrogels [ 9 ], fluorescent probes [ 10 , 11 , 12 ], nitroxide radical probes [ 13 ], the preparation of adsorbent or solid fluorescent materials [ 14 ], room-temperature phosphorescence (RTP) [ 15 , 16 ], light-harvesting systems [ 17 ], nanocapsules [ 18 ], nanofiltration membranes [ 19 ] molecular machines [ 20 , 21 , 22 ] reductive catalysis of CO 2 [ 23 ], and gold recovery [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Tao et al 35 reported that [AuCl 4 ] − anions could be imprisoned inside two slightly different supramolecular frameworks composed of cucurbit [8]uril (CB [8]). These authors also demonstrated 36 the selective recovery and detection of [AuCl 4 ] − with smaller cucurbit[n]urils (n = 5− 7) based on outer-surface interactions. At one and the same time, we have finished, quite independently, our own research program on gold recovery using cucurbit [6]uril (CB [6]).…”
Section: ■ Introductionmentioning
confidence: 99%